Transit stories - Chua, Allan Stephen (2005)
This thesis is composed of several short stories in English, set in Metro Manila, with an introduction which discusses the factors that contributed to the development of these stories. The introduction also includes a brief discussion of city fiction, its definitions and characteristics.